Microstructural Evolution of Al-1Fe (Weight Percent) Alloy During Accumulative Continuous Extrusion Forming - Wang, Xiang; Guan, Ren-Guo; Tie, Di; Shang, Ying-Qiu; Jin, Hong-Mei; Li, Hong-Chao (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2018)
As a new microstructure refining method, accumulative continuous extrusion forming (ACEF) cannot only refine metal matrix but also refine the phases that exist in it. In order to detect the refinements of grain and second phase during the process, Al-1Fe (wt pct) alloy was processed by ACEF, and the microstructural evolution was analyzed by electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). Results revealed that the average grain size of Al-1Fe (wt pct) alloy decreased from 13 to 1.2 μ m, and blocky Al 3 Fe phase with an average length of 300 nm was granulated to Al 3 Fe particle with an average diameter of 200 nm, after one pass of ACEF. Refinement of grain was attributed to continuous dynamic recrystallization (CDRX), and the granulation of Al 3 Fe phase included the spheroidization resulting from deformation heat and the fragmentation caused by the coupling effects of strain and thermal effect. The spheroidization worked in almost the entire deformation process, while the fragmentation required strain accumulation. However, fragmentation contributed more than spheroidization. Al 3 Fe particle stimulated the formation of substructure and retarded the migration of recrystallized grain boundary, but the effect of Al 3 Fe phase on refinement of grain could only be determined by the contrastive investigation of Al-1Fe (wt pct) alloy and pure Al.